Informe jurídico sobre la Resolución N° 074-2023-SUNAFIL/TFL-Primera Sala - Torres Seperak, Daniela Katiuska (2025)
This case seeks to resolve the scope of the analysis carried out by the labor inspection court in matters of sexual harassment in the workplace, in which it is questioned whether the legal development, from the functions and competencies, limit it to reviewing formal aspects based on compliance with the social and labor regulations from the respect of the principle of legality or if they also involve the observation of substantive elements. Likewise, within the aforementioned analysis, the role of the company as responsible for generating a safe and healthy environment is questioned, as well as an objective investigation to safeguard the affected rights of the harassed person. For this purpose, this report made use of the normative materials on labor matters, both national and international, as well as the available doctrine and jurisprudence. Given the above, it was possible to conclude that the court is empowered to analyze what was challenged in the appeal for review, even if it considers the evidence provided in the process, expanding its effectiveness not only in the application of fines but also providing a preventive approach and guaranteeing the rights related to the dignity, health and integrity of employees. Finally, the analysis of the obligation determined in this type of case also has an impact on the company's actions, even before the configuration of any harassing conduct such as the one mentioned, as well as in the process of investigation and final decision regarding the same.